THE PERCEPTION OF THE ENGLISH CLUB MEMBERS OF THE ENGLISH DEPARTMENT STUDENTS ASSOCIATION (EDSA) TOWARD THEIR CLUB - Destrianti, Eva; Sabaruddin, Syafrizal; Hati, Gita Mutiara (Journal of English Education and Teaching, 2018)
This research is a descriptive quantitative research which aimed to investigate positive or negative perception of the English club members of EDSA (English Department Students Association) toward their club in cognitive, affective and connative components. The population of this research was all members of the EDSA’s English club. The samples were 40 respondents and the instrument was a questionnaire. The questionnaire consists of 25 items of three components which covered six variables like materials, activities, coach, schedule, place and English skill improvement. The result shows that 88.2% of the respondents had positive perception toward their English club, far much higher than negative one which was only 11.8%. Therefore, it can be concluded that English club was run well as the members had positive perception toward their club in all of the components